2019
DOI: 10.1088/1748-9326/ab502c
|View full text |Cite
|
Sign up to set email alerts
|

A green infrastructure spatial planning model for evaluating ecosystem service tradeoffs and synergies across three coastal megacities

Abstract: A growing number of cities are investing in green infrastructure to foster urban resilience and sustainability. While these nature-based solutions are often promoted on the basis of their multifunctionality, in practice, most studies and plans focus on a single benefit, such as stormwater management. This represents a missed opportunity to strategically site green infrastructure to leverage social and ecological co-benefits. To address this gap, this paper builds on existing modeling approaches for green infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 51 publications
0
37
0
3
Order By: Relevance
“…Majidi et al (2019) assessed the effectiveness of various nature-based solutions based on a range of criteria covering both hydrologic and urban cooling services. Meerow (2019) examined synergistic 'hotspots' that maximise co-benefits in Manila and found that the stormwater management service correlated positively with three other services: reducing social vulnerability, reducing the urban heat island effect and improving air quality. Other authors have examined which co-benefits should be prioritised.…”
Section: Assessing Co-benefitsmentioning
confidence: 99%
“…Majidi et al (2019) assessed the effectiveness of various nature-based solutions based on a range of criteria covering both hydrologic and urban cooling services. Meerow (2019) examined synergistic 'hotspots' that maximise co-benefits in Manila and found that the stormwater management service correlated positively with three other services: reducing social vulnerability, reducing the urban heat island effect and improving air quality. Other authors have examined which co-benefits should be prioritised.…”
Section: Assessing Co-benefitsmentioning
confidence: 99%
“…75 There is an opportunity for green infrastructure to support stormwater management, flood mitigation, and other ecosystem services and social benefits including reducing social vulnerability, access to green space, and improved mental health. 76 Nevertheless, how power, privilege, planning policies, and development patterns affect infrastructure management have to be examined. 77 Infrastructures are the fundamental building blocks of neighborhoods.…”
Section: Social Vulnerability Mileti 39mentioning
confidence: 99%
“…Despite this, clearer understanding of best management practices within GI scheme design is needed to ensure long term functioning and to mitigate against failure. Tools for evaluating GI success and providing an evidence base for GI implementation are beginning to be complied for GI schemes (e.g., Kapetas & Fenner, 2020; Meerow, 2019), but GI should be designed to be resilient to future changes, implying that GI should possess adaptive capacity and, ideally, the ability to naturally respond to changes in the surrounding areas (Johnson et al, 2019), much like a natural system.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…The European Commission highlighted the potential multiple benefits of GI, defined as “ a strategically planned network of high quality natural and semi‐natural areas with other environmental features, which are designed and managed to deliver a wide range of ecosystem services and protect biodiversity in both rural and urban settings ” (European Commission, 2013). While urban GI are often presented as multifunctional assets, in practice, most schemes focus on a single benefit, such as stormwater management (Kabisch et al, 2016; Meerow, 2019). As such, GI is a key component of the surface water management strategies of many progressive global cities at risk of urban flooding (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%